RANCANG BANGUN SISTEM INFORMASI MONITORING MAGANG PADA PROGRAM STUDI SISTEM INFORMASI UNIVERSITAS PGRI KANJURUHAN MALANG - Ramadhani, Aldiansa Kautsar; Susanto, Gaguk; Dwanoko, Yoyok Seby (JOURNAL OF INFORMATION TECHNOLOGY, INFORMATION SYSTEMS AND COMMUNICATIONS, 2025)
Internship is a process to apply the knowledge or competencies acquired during the academic period directly in the working environment. The Information Systems Program at PGRI Kanjuruhan University Malang is one of the programs that require all students to take Internship courses. The effective implementation of an internship program requires a solution that can provide timely monitoring and reporting, as well as transparency regarding the internship activities of students. Based on these issues, an Internship Monitoring Information System is designed to address these problems in order to improve efficiency and effectiveness in managing internship program activities. This Internship Monitoring System is built using ÂÂthe CodeIgniter Framework and follows the Prototyping development model. From the research results, an application in the form of an Internship Monitoring Information System is generated, which can monitor students' internship activities. The results of the User Acceptance Test (UAT) with an overall average score of 93.17% indicate that the designed Internship Monitoring System can assist in managing the internship program in the Information Systems Program at UNIKAMA.